Algorithm for Optimal Two-Link Trajectory Planning in Evasion from Detection Problem of Mobile Vehicle with Non-Uniform Radiation Pattern (Advances in Systems Science and Applications, 2021)
The problem of an optimal PP/TP (path/trajectory planning) evasion of a mobile vehicle from the detection is considered. The objective is to minimize the risk of a moving vehicle being detected by a static sensor when moving between two specified points on the plane. Detection is based on the primary acoustic field emitted by a vehicle with an inhomogeneous radiation pattern. An algorithm for finding a two-link optimal trajectory is proposed. The optimal trajectory and the law of speed of a mobile vehicle, as well as the value of the criterion, are found.